Artificial General Intelligence: Advancements, Challenges, and Future Directions in AGI Research - Gokul Yenduri; Ramalingam Murugan; Praveen Kumar Reddy Maddikunta; Sweta Bhattacharya; Devulapalli Sudheer; Bharath Bhushan Savarala (IEEE Access)
Artificial General Intelligence (AGI) is a transformative shift in artificial intelligence that aims to match human-like reasoning, flexibility, and self-learning. Unlike Narrow AI, which is capable of performing only a limited set of tasks, AGI aspires to handle any intellectual task by exhibiting human-like learning, reasoning, and behavior. This enables AGI to offer extraordinary potential in various domains such as healthcare, education, transportation, and more. This paper provides a comprehensive review of the fundamental concepts, applications, and challenges associated with AGI’s development. This systematic review of the literature explored AGI’s transformative potential, from personalized healthcare and adaptive learning systems to advanced autonomous vehicles and predictive analytics. Although, AGI has great potential, multiple challenges, such as ethical issues, data privacy, and other technical challenges, must be addressed before its launch in the real world.